Management of combined massive burn and blast injury: A 20-year experience - Zheng, Xing-feng; Zhu, Feng; Fang, He; Xu, Da-yuan; Xu, Long; Chen, Tian-sheng; Zheng, Yong-jun; Xiao, Shi-chu; Xia, Zhao-fan (Burns, 2020)
•The diagnosis of blast lung injury combined with massive burn is challenging.•A comprehensive treatment approach is recommended in this combined injury.•Although difficult, the overall mortality of this combined injury can be reduced. Blast injuries are complex types of physical trauma resulting from direct or indirect exposure to an explosion, which can be divided into four classes: primary, secondary, tertiary, and quaternary. Primary blast injury results in damage, principally, in gas-containing organs such as the lungs (blast lung injury, BLI). BLI is defined as radiological and clinical evidence of acute lung injury occurring within 12h of exposure to an explosion and not due to secondary or tertiary injury. BLI often combines with cutaneous thermal injury, a type of quaternary blast injury, either in terrorist bomb attacks or in civilian accidental explosions. This report summarizes our experience in the management of combined massive burn and BLI at a Shanghai Burn Center in China. A retrospective observational analysis of clinical data was performed for massive burn patients with or without BLI during a 20-year interval. Patient characteristics, causes of injury, clinical parameters, management, and outcomes were recorded and evaluated. A total of 151 patients (120 males and 31 females) with severe burn injury (≥50% TBSA) treated at the Burn Center of Changhai Hospital in Shanghai between July 1997 and June 2017 were enrolled in this study. Their mean age was 38.6±17.8 (3–75) years. Among them, 28 patients had combined BLI and burn injury and 39 patients had no BLI or smoke inhalation injury (non-BLI-SII). No significant difference was observed in the burn area or full-thickness burn area between the two groups. The lowest PaO2/fraction of inspired oxygen (FiO2) ratio during the first 24h in BLI patients was significantly lower than that in non-BLI-SII patients. Exudative changes were observed by X-ray radiography in all BLI patients but not in non-BLI-SII patients within 6h after injury. A significantly higher proportion of colloids were used for fluid resuscitation in BLI patients than that in non-BLI-SII patients. A higher proportion and longer time of mechanical ventilation were needed for BLI patients than those for non-BLI-SII patients, and a higher proportion of patients received sedative agents in the BLI group than those in the non-BLI-SII group. The first escharectomy was performed relatively later in BLI patients than in non-BLI-SII patients because of more time taken by BLI patients to recover from lung injury. The length of ICU and hospital stay in BLI patients was significantly longer than that in non-BLI-SII patients. No significant difference in the overall mortality was detected between these two groups. It is a formidable challenge for clinicians to diagnose and manage massive burn patients combined with BLI. A comprehensive treatment approach is strongly recommended, including fluid resuscitation, airway management, mechanical ventilation, and surgical treatment. Given the high mortality of massive burn patients combined with BLI even in a recognized burn center, more prospective studies are encouraged to assess more effective strategies for the treatment of such patients.